Multispectral and Multi‐instrument Observation of TIDs Following the Total Solar Eclipse of 21 August 2017. Issue 5 (25th May 2019) - Aryal, Saurav; Geddes, George; Finn, Susanna C.; Mrak, Sebastijan; Galkin, Ivan; Cnossen, Ingrid; Cook, Timothy; Chakrabarti, Supriya
Abstract: Wave‐like structures in the upper atmospheric nightglow brightness were observed on the night of 22 August 2017, approximately 8 hr following a total solar eclipse. These wave‐like perturbations are signatures of atmospheric gravity waves and associated traveling ionospheric disturbances (TIDs). Observations were made in the red line (OI 630.0 nm) and the green line (OI 557.7 nm) from Carbondale, IL, at 2–10 UTC on 22 August 2017. Based on wavelet analyses, the dominant time period in both the red and green lines was around 1.5 hr. Differential total electron content data obtained from Global Positioning System total electron content measurements at Carbondale, IL, and ionospheric parameters from digisonde measurements at Idaho National Laboratory and Millstone Hill showed a similar dominant time period. Based on these observations and their correlation with geomagnetic indices, the TIDs appear to be associated with geomagnetic disturbances. In addition, by modeling the ionosphere‐thermosphere system's response to the eclipse, it was seen that while the eclipse enhanced the O/N2 ratio and electron density (N e ) at 250 km during our observation period, it did not affect the TIDs. Vertical (7 m/s) and meridional (616 m/s) phase velocities of the TIDs were estimated using cross‐correlation analysis between red and green line brightness profiles and spectral analysis of the differential total electron content keogram, respectively. This provides a method to characterize the three‐dimensional wave properties of TIDs. Key Points: Meridional and vertical wave properties of LSTIDs are characterized based on multi‐instrument observations Effects of the solar eclipse that preceded the LSTID are also studied based on modeling Model estimates suggest that the IT system was preconditioned due to the eclipse but there is no evidence of this affecting the LSTIDs